The Effect of Jealousy on Cyber Dating Violence in People Who Have A Long Distance Relationship - Valencia Vina Winata; Ersa Lanang Sanjaya (Fakultas Psikologi Universitas Pancasila, 2020)
The purpose of this research is to study the role of jealousy that can increase emergence of cyber dating violence behavior through electronic devices by individuals who undergoing long distance dating relationship with their dating partner . The subjects of this study is 166 individuals who had or undergoing long distance relationship with their romantic dating partner. This research use quantitative research with simple regression test. Measuring instruments used in this study include cyber dating abuse questionaire owned by Borrajo (2015) and Multidimensional Jealousy owned by Pfeiffer and Wong (1989). The results of this study showed that jealousy has a significant role that can increase emergence of cyber dating violence and behavioral jealousy has influence with effective contributions of 22.6% on the occurrence of cyber dating violence (R2 = 0.226; p = 0.000).